Efektivitas Peran Auditor Internal di UIN Syarif Hidayatullah Jakarta yang Ditunjukkan Oleh PP No. 60 Tahun 2008: “Sistem Pengendalian Intern Pemerintah (SPIP)” - Yusar Sagara (Faculty of Economic and Business, 2015)
The effectiveness of the Internal Auditor's role in UIN Syarif Hidayatullah Jakarta Shown By Regulation No. 60 of 2008: